Diversidade, cidadania e direitos : práticas docentes e formação de professores/as em relação a uma disciplina de núcleo comum da Universidade Estadual de Goiás, nos Cursos Superiores de Tecnologia - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This study is a research result developed along with the Post-graduate Program in Education, Language, and Technology at State University of Goiás –UEG (PPG-IELT), and it is specifically limited to Education, Society and technology. The object of research involves the subject Human Rights, Diversity and Citizenship, given at State University of Goiás-UEG, becoming an obligatory course, since 2015, ranging all higher education offered by the institution, therefore receiving the classification of a common core course within the curriculum mapping of the University. The answer sought emerges within the following indignation: What are the senses (qualification and training) attributed for the professors within the Human Rights, Diversity and Citizenship course, offered by a higher education of technology at State University of Goiás? As a general purpose, we aim to: understand and exhibit the senses attributed for the professor within the Human Rights, Diversity and Citizenship course, who are part of the common curriculum of higher education of Technology at State University of GoiásUEG. Thus, it is part of building a theoretical and conceptual framework and the relation between education and Rights, Diversity and Citizenship course, as well as its inclusion within the pedagogical process as a strong need of being part of the common core courses at UEG; right after, it is presented the profiles of all teaching professors who participated in this research. And for last, we focused on the understanding of how this subject was organized, interpreted and given by the professor, as well as the perceptions of the professors who were in charge of teaching, considering their specificity and indispensability, in which must consider the correct pedagogical and theoretical training of these professors. The qualitative research method along with the phenomenological approach was used in order to perform this study, aiming the use of the exploratory research as well, according to the technical, bibliographic and empirical procedures. A database was made possible after a narrative interview with two college managers who were working along with the staff of the college course counselors, in order to comprehend the main objective of the chosen course within technology, and through a survey applied to the professors who were teaching this course in Higher Education of Technology from 2015 to 2018.Thus, we could notice that it comes from the study of the essential terms within the course and its correlations with education as a social practice. We were able to emphasize that the proposal of the course reveals to be relevant for the qualification of individuals for being the ideal space in building a theoretical and conceptual framework, in which raise fundamental question debates nowadays, and that the chosen course was derived from a national politics within the fight against discrimination, as well as the achievement and consciousness of the fundamental rights of the citizen. This research shows that the qualification of the professors for teaching this course, must be thought by higher authorities of the University, in order to promote the best result possible; that the professors find difficulties in relation to the focus within the given course, due to its amplitude and the lack of clear criteria, in which can make it possible to resemble its importance within the qualification of an individual.
Human rights, diversity and citizen ship: human rights, diversity and citizenship: professors’ concepts in relation to a common core course at State University of Goiás, within Higher Education courses of Technology
Keywords: Educação e Cidadania; Educação e Diversidade; Educação e Direitos humanos; Education and Citizenship; Education and Diversity; Education and Human rights; CIENCIAS HUMANAS::EDUCACAO; FUNDAMENTOS DA EDUCACAO::SOCIOLOGIA DA EDUCACAO